Sexual assault and harassment of doctors, by doctors: a qualitative study. Issue 8 (29th May 2019) - Stone, Louise; Phillips, Christine; Douglas, Kirsty A
Abstract : Context: Although sexual harassment frequently occurs in medical education and medical workplaces, doctors who have been sexually harassed or assaulted by other doctors remain a largely invisible population. This study aimed to identify, using personal accounts, the impact on doctors of sexual harassment and assault by doctors in the workplace. Methods: This narrative study used in‐depth interviews, legal reports and victim impact statements, tracing trajectories from the event's pre‐history to its aftermath and impact on professional practice. Participants were six Australian women doctors who had been subjected to one or more non‐consensual sexual acts through coercion or intimidation by another doctor in their working environments, within hospital training programmes. Results: All women identified long‐term personal and professional impacts of their experience. Three women had never reported the abuse. The meaning and impact of sexual abuse for the doctors followed a trajectory with discrete phases: prelude, assault, limbo, exposure and aftermath. Discounting the event and its impacts, and returning to the workplace were characterised as 'being professional'. Those who sought legal restitution said it damaged their personal well‐being and their standing among fellow doctors. Discussion: Understanding the phases of experience of abuse enables the development of effective interventions for different phases. Interventions to minimise the risk of occurrence of sexual abuse must be distinguished from interventions to increase reporting rates, and interventions to mitigate harm and impact on victims' futures. Idealised notions of professionalism can act as obstacles to doctors responding to sexual abuse. Abstract : Conceptions of professionalism, gendered relations and hierarchical relationships in medicine are shown in this study to influence sexual harassment and assault of doctors by doctors.